PENULISAN ETUDE-ETUDE MUSIK TALEMPONG UNGGAN (Sebuah Usaha Pembelajaran Musik Tradisi Berbasis Literatur) - MK, Asri (Humanus, 2014)
â€œTalempong ungganâ€, a traditional music from Minangkabau community particularly in Unggan, Sumpur Kudus, Sijunjung Regency, West Sumatera Indonesia is classified into genre of â€œtalempong duduakâ€ (rea). Due to its special musical concept and the playing technics, this traditional music is selected as a practising course in the Karawitan Department of Indonesian Institute of Art (ISI) Padang Panjang since 1993 till now. In a system of class learning with many students, Talempong Unggan definitely needs supporting methods and learning technics suitable for the course where the students can reach their maximum skills. All the melody of â€œtalempong ungganâ€ that has been made as a material of practice is transcribed to the system of numeric notation and rhythm motive of â€œgendangâ€ and â€œaguangâ€ which is written into signs and special notation. All of qualitative data is formulated into finding methods, technics and etude of learning ensamble of Talempong Unggan the traditional music that learned in Karawitan Department of ISI Padang Panjang. Key words: Talempong Unggan, Methods, Technics, Etude